2017
DOI: 10.1016/j.nano.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Poly lactic-co-glycolic acid controlled delivery of disulfiram to target liver cancer stem-like cells

Abstract: Disulfiram (DS), an anti-alcoholism drug, shows very strong cytotoxicity in many cancer types. However its clinical application in cancer treatment is limited by the very short half-life in the bloodstream. In this study, we developed a poly lactic-co-glycolic acid (PLGA)-encapsulated DS protecting DS from the degradation in the bloodstream. The newly developed DS-PLGA was characterized. The DS-PLGA has very satisfactory encapsulation efficiency, drug-loading content and controlled release rate in vitro. PLGA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 50 publications
1
57
0
Order By: Relevance
“…Epirubicin-adsorbed nanodiamonds displayed high efficacy in inducing the elimination of chemoresistant LCSCs [179] . Poly lacticco-glycolic acid-encapsulated disulfiram strongly inhibits LCSCs and has a synergistic cytotoxicity with 5-FU or sorafenib [180] . Gao et al [181] developed a GPC3-targeted CAR and found that it obviously suppressesed HCC growth.…”
Section: Treatment Targeting Lcscsmentioning
confidence: 99%
“…Epirubicin-adsorbed nanodiamonds displayed high efficacy in inducing the elimination of chemoresistant LCSCs [179] . Poly lacticco-glycolic acid-encapsulated disulfiram strongly inhibits LCSCs and has a synergistic cytotoxicity with 5-FU or sorafenib [180] . Gao et al [181] developed a GPC3-targeted CAR and found that it obviously suppressesed HCC growth.…”
Section: Treatment Targeting Lcscsmentioning
confidence: 99%
“…Therefore, a drug delivery system which protects DSF from metabolism in the blood stream would expedite its translation into the clinic as a treatment for NSCLC. We recently demonstrated that PLGA nanoparticles can extend the half-life of DSF in blood from under 2 minutes to 7 hours [46]. To further develop our DSF-loaded PLGA nanoparticles it is imperative that we understand how the choice of formulation and sonication time influences the ability of the PLGA nanoparticles to protect the DSF from degradation in the bloodstream.…”
Section: The Ability Of the 10% W/w Dsf-loaded Plga Nanoparticles To mentioning
confidence: 99%
“…The DSF-loaded PLGA nanoparticles in combination with copper significantly inhibited the liver CSC population and demonstrated very promising anticancer efficacy and anti-metastatic effect in a liver cancer mouse model [46].…”
Section: Introductionmentioning
confidence: 97%
“…Many literatures have reported that PCL or PLGA could be served as compatible biomaterials to build nanocarrier-based delivery systems [38][39][40]. Herein, PCL was utilized to stabilize hydrophobic core, while mPEG-PLGA was used to improve the solubility of nanoparticles owing to pegylation [41][42][43][44][45] (Fig.…”
Section: Preparation and Characterization Of The Nanoformulationsmentioning
confidence: 99%